PERBEDAAN PRAKTIK MANAJEMEN LABA PADA BANK UMUM SYARIAH DAN BANK KONVENSIONAL (Studi Kasus pada Bank Umum Syariah dan Bank Konvensional yang terdaftar di BI tahun 2013-2015) - Kurniasari, Dhifa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study tries to identify the indication of earnings management practices in conventional and sharia banks and the differences between the two. The objects of this study are conventional and sharia banks listed in the Central Bank of Indonesia during 2013-2015. Using purposive sampling, 168 datas conventional banks and 30 datas sharia banks were selected as the sample. The earnings management is measured using discretionary accrual approach and Modified Jones Model. The data were analyzed through one sample t-test and independent sample t-test using SPSS. The result of this study shows that sharia banks are not likely to carry out earnings management because it has an average value of discretionary accruals very low, while conventional bank commit earnings management, which was shown by negative discretionary accrual values observable during the research period. However, there is no significant difference of earnings management between the two, because the difference in average value of discretionary accrual is very thin. This proves that earnings management is done to meet Central Bank of Indonesia regulations and not for opportunistic reasons.Keywords: earnings management, discretionary accrual, sharia bank, conventional bank